Teaching for Fostering Creativity in Higher Education for Facing The Global Competition : A Systematic Literature Review - Maridha Normawati; Farida Kurniawati (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to analyze the facilitators and barriers that influence teaching to foster students' creativity in higher education and how the implementation made by the university encourages creativity in students. This study used the systematic literature review method with PRISMA procedure based on the following criteria: The literature was published in Taylor and Francis and ProQuest from 1997 to 2022 and written in English. Literature extraction and synthesis were carried out from 19 articles and then analyzed using content analysis. Results showed more factors, namely teacher beliefs, positive attitudes of teachers toward creativity, collaboration in learning, group discussions, providing training, lecturers teaching method to instill a growth mindset, providing assessments according to actual situations, and the use of technology that encourages lecturers to foster creativity rather than the barriers. In addition, the implementation made by universities for fostering creativity includes training programs and using various technology-based creative applications adapted to the characteristics of the major disciplines.